Strengthening institutional governance and fraud prevention in the management of village-owned enterprises - Azna Abrory Wardana; Setiawan Noerdajasakti; Solehudin; Muhammad Najih Vargholy (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Sumberkerang Village and Karang Pranti Village have tourist attractions that are then managed as joint tourist attraction business units. The results of field observations indicate that there is a lack of transparency in the management of BUMDes finances, as the BUMDes financial report is only accessible to the BUMDes chairman and treasurer. There is a lack of clarity in the description of duties between the BUMDes chairman and the Village Government. There is manipulative data on Village Original Income, especially income through BUMDes where income does not match reality. The method used is qualitative descriptive with data collection through interviews with several informants and discussion forums involved in BUMDes management, and providing training in BUMDes management that is more transparent and accountable. Efforts were made by providing training and mechanisms for BUMDes financial fraud prevention models by managing finances according to the regulations set, where each income must be recorded according to reality, and a Standard Operating Procedure for reporting BUMDes management is prepared. Further fraud prevention is carried out through weekly supervision by the BPD to ensure that BUMDes management is conducted according to existing systems and regulations. This service, through socialization and training for partners, can provide benefits so that they can carry out financial activities according to established regulations, and village communities can also participate in supervising BUMDes financial management.